"I (might be) just that good": Honest and deceptive impression management in employment interviews. Issue 4 (2nd August 2018) - Bourdage, Joshua S.; Roulin, Nicolas; Tarraf, Rima
Abstract: Applicant use of impression management (IM) tactics plays a central role in employment interviews. IM includes behaviors intended to create an impression of competence and likability, and avoid negative impressions. Applicants can influence interviewers' impressions using both honest and deceptive IM, but measurement of IM has yet to distinguish these two constructs. The goal of the present research was to develop a self‐report Honest Interview Impression Management (HIIM) measure and use this to investigate differential antecedents and consequences of honest and deceptive IM. We report the results of five independent studies (total N = 1, 470 interviewees). Studies 1–3 detail the creation of a self‐report measure of honest IM. Studies 4 and 5 utilize this measure to understand the relations between honest and deceptive IM, and their antecedents and consequences. Results demonstrate that honest and deceptive IM are positively related but distinct constructs that have unique antecedents (i.e., age, individual differences, attitudes, situational, and target characteristics) and differentially impact interview outcomes and ratings. Finally, we present a short measure of honest and deceptive IM to be used for time‐sensitive data collection.